2017
DOI: 10.1080/21645515.2016.1265715
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of an adjuvanted herpes zoster subunit candidate vaccine in adults ≥ 50 years of age with a prior history of herpes zoster: A phase III, non-randomized, open-label clinical trial

Abstract: This phase III, non-randomized, open-label, multi-center study (NCT01827839) evaluated the immunogenicity and safety of an adjuvanted recombinant subunit herpes zoster (HZ) vaccine (HZ/su) in adults aged ≥ 50 y with prior physician-documented history of HZ. Participants (stratified by age: 50–59, 60–69 and ≥ 70 y) received 2 doses of HZ/su 2 months apart and were followed-up for another 12 months. Anti-glycoprotein E (gE) antibodies were measured by enzyme-linked immunosorbent assay before vaccination and 1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
(20 reference statements)
1
27
0
3
Order By: Relevance
“…The subunit vaccine is also immunogenic and safe in people that have had a previous episode of HZ. 67 …”
Section: Current Developmentsmentioning
confidence: 99%
“…The subunit vaccine is also immunogenic and safe in people that have had a previous episode of HZ. 67 …”
Section: Current Developmentsmentioning
confidence: 99%
“…In another study, a group of patients with a history of herpes zoster infections showed a very good production of IgE antibodies with RZV. The study concluded that vaccine reactogenicity and safety are not impacted by a prior history HZ infection . There have been no studies yet with dialysis patients or patients with CKD.…”
Section: Varicella/zostermentioning
confidence: 96%
“…In the countries where it is currently available, RZV in 2 doses between 2‐6 months apart is recommended in all susceptible patients …”
Section: Practical Recommendations For Vaccinating Schedules In Dialymentioning
confidence: 99%
“…Die Immunogenität und Sicherheit einer HZ/su-Impfung bei ≥ 50-jährigen Patienten nach einer vorausgegangenen HZ-Erkrankung wurde in einer nicht-randomisierten, offenen Multicenterstudie in Kanada und Russland zwischen Juni 2013 und November 2014 untersucht. 24 Von den Teilneh-merInnen der Studie (n = 96) waren 68 % (n = 65) innerhalb der vergangenen 4 Jahre an einem HZ erkrankt, keiner von ihnen wies jedoch aktive HZ-Krankheitszeichen auf. Bei 19 % (n = 18) lag die HZ-Episode 5 -9 Jahre zurück und bei 14 % (n = 13) war der HZ vor ≥ 10 Jahren aufgetreten.…”
Section: Hz/su-impfung Nach Vorausgegangener Hz-erkrankungunclassified